Effect of environments and normal loads on tribological properties of nitrided Ni45(FeCoCr)40(AlTi)15 high-entropy alloys. (1st April 2020) - Lan, L.W.; Wang, X.J.; Guo, R.P.; Yang, H.J.; Qiao, J.W.
Abstract: The tribological properties of nitrided Ni45 (FeCoCr)40 (AlTi)15 high-entropy alloys (HEAs) were investigated in air and simulated acid rain under different normal loads (5, 7, 10, and 12 N) at ambient temperature. The results revealed that as-cast HEAs were only composed of FCC phase, while the volume fraction of FCC phase in the nitrided alloys was significantly reduced. Moreover, the hard phases of AlN, CrN, Fe4 N, and TiN phases were formed in the nitrided alloys. The thickness of the nitriding layer was about 8.4 μm. The hardness increased from 8.7 GPa in as-cast alloys to 14.5 GPa in the nitrided alloys. In addition, under the same conditions, the friction coefficient of the nitrided alloys was higher than that of as-cast alloys, but the wear rate was generally lower than that of as-cast alloys. Furthermore, the wear rate of the nitrided alloys was the lowest in acid rain due to the lubrication, cleaning, and cooling in the liquid environment. In air, dominating wear mechanisms in as-cast and nitrided alloys were abrasive, delamination, and adhesive wears. And, the wear mechanism of as-cast and nitrided alloys in acid rain was mainly abrasive and corrosion wears.